Bryant & May : peculiar London - Fowler, Christopher (Fowler, Christopher. Bryant & May mysteries., 2022)
"Thinking of a jaunt to England? Let Arthur Bryant and John May, London's oldest police detectives, show you the oddities behind the city's façades in this tongue-in-cheek travel guide"--